Avaliação da qualidade dos serviços das operadoras de telefonia na região de Curitiba - Lima, Cintia Klaumann (2015)
We live in the information age, where the telecommunications systems have been the instrument of integration and economic development. In this context telephone operators has been gaining meaning prominent. This work is to present the importance of quality indicators for measuring the performance and quality of services provided by fixed and mobile operators in the region of Curitiba. To do so will be initially presented a vision and the concept of the indicators used to measure the performance of operators. Following the most relevant services for customers and finally there will be an analysis of the quality of services provided by operators based on these indicators. This way, you can assess the quality of services also showing which providers have the highest rates of complaints among consumers. The fixed and mobile sectors were analyzed. With this study it is concluded that the indicators there are disclosed, but do not reflect how customers evaluate the quality and are not all operators that invest in a system of continuous improvement and a process of after-sales quality thus creating dissatisfaction of their clients.